Inclusive Education as a Manifestation of the Value of Mercy in Islamic Education - Bagus Jordan; Bagas Agamy Bakti; Muhammad Syahrul Hidayatullah Pasaribu; Herlini Puspika Sari (Yayasan Zia Salsabila, 2026)
This study aims to formulate a theoretical model regarding the relevance and strategic role of educational philosophy in redefining the meaning of learning amidst the dominance of digital technology. The central issue is how educational philosophy can offer a robust conceptual framework for navigating rather than simply exploiting the digital ecosystem. This study uses a qualitative approach with library research methods, focusing on philosophical-conceptual analysis. The research findings show that technology triggers a shift in the meaning of learning from merely a one-way transfer of information to an active process of knowledge construction (constructivism), so that the role of teachers is transformed into critical facilitators. The relevance of the core of philosophy, including axiology, epistemology, and ontology, is becoming increasingly stronger. Epistemology serves as a bulwark against the “Digital Truth Crisis” by demanding critical literacy, while axiology provides a moral compass for issues of digital ethics. In its synthesis, the meaning of enriched learning is a metacognitive process that combines technical skills with moral maturity (wisdom). Educational philosophy plays a moral and intellectual role that ensures that technology remains within the corridor of the main goal of education: holistic human development.